The Effect of the Deformity Genetic Background of the Breeders on the Spawning Quality of Gilthead Seabream (Sparus aurata L.) - Lorenzo-Felipe, Álvaro; Shin, Hyun Suk; León-Bernabeu, Sergio; Pérez-García, Cathaysa; Zamorano, María Jesús; Pérez-Sánchez, Jaume; Afonso-López, Juan Manuel (Frontiers in Marine Science, 2021)
High quality seeds are strongly demanded for aquaculture on-growing companies. Due to the management variation between and within hatcheries, they oversize their broodstocks in order to warranty the minimum of required fries. However they do not normally consider the genetic background of breeders. This work reports, for the first time in gilthead seabream, how the genetic background of breeders for the presence-absence of any deformity at commercial size influences their spawning quality. Genetically deformed breeders presented shorter spawning periods, lower oocyte yield and consequently lower larvae YSR than genetically normal ones. Larvae YSR is essentially determined by oocyte yield and viability rate. Moreover, it describes how the genetic effect gains importance in the intermediate spawning periods, when spawning is generally considered optimal for industries. In conclusion, genetic background quality of breeders is determinant to modulate the spawning quality, improving the profit of the companies in this species.